Low-Threshold Q-Switched Erbium-Doped Fiber Laser Using Molybdenum Disulphide Saturable Absorber Prepared Through Evaporitic Formation - Chong, W.Y.; Yap, Y.K.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2015)
An MoS2-based Q-switched erbium-doped fiber laser with a low threshold and a wide range of repetition rate was successfully demonstrated. Bulk MoS2 flakes were formed by reducing the volume of MoS2-in-ethanol solution through evaporation at elevated temperature. The MoS2 flake was transferred mechanically onto a fiber ferrule to form a fiber saturable absorber. The threshold for self-start Q-switching was as low as 8.0 mW. The laser was capable of producing average output power, repetition rate, and pulse energy as high as 10.7 mW, 71.5 kHz, and 160 nJ, respectively. The repetition rate has a wide range of frequencies over 60 kHz. The shortest pulse duration obtained was 2.79 mu s.